Beyond Weight Reduction: An Updated Systematic Review and Meta-Analysis of Metabolic Syndrome Components and Metabolic Dysfunction-Associated Steatotic Liver Disease Outcomes After Endoscopic Sleeve Gastroplasty - Alexander Herner; Simon Nennstiel; Christoph Schlag; Andreas Kremer; Luc Biedermann; Gerhard Rogler; Michael Doulberis (Journal of Clinical Medicine, 2026)
Background: Endoscopic sleeve gastroplasty (ESG) is a minimally invasive option for weight reduction, but its effect on metabolic syndrome (MetS) and metabolic dysfunction-associated steatotic liver disease (MASLD) is less well characterized. Methods: Following PRISMA, we searched five databases to November 2025 (PROSPERO CRD420261283041) for adults with obesity undergoing ESG with ≥6-month follow-up. Continuous outcomes were pooled as mean differences (MDs) using DerSimonian–Laird random-effects models with Hartung–Knapp–Sidik–Jonkman sensitivity analysis. As MetS resolution was inconsistently defined, the primary outcome was post hoc operationalised as change in individual MetS components. Results: Of 858 records, 12 studies (4452 patients; two randomised) were included. At 12 months, ESG was associated with lower glycated haemoglobin (MD −0.33%), HOMA-IR (MD −3.52), triglycerides (MD −25.56 mg/dL), low-density lipoprotein cholesterol (MD −6.94 mg/dL), alanine aminotransferase, and non-invasive steatosis/fibrosis indices; aspartate aminotransferase did not change significantly. Total body weight loss was 16.54% at 12 months and 14.21% at 36 months. Liver stiffness (two studies, differing windows) is described narratively, not pooled. Heterogeneity was often substantial; certainty was low to very low. Conclusions: ESG was associated with metabolic and hepatic improvements alongside substantial weight loss; a weight-independent hepatic effect cannot be established, and randomised trials with histological endpoints are needed.